Measles, mumps, and rubella vaccination coverage in children younger than 5 years attending a paediatric emergency department in Manchester, UK: a cross-sectional observational study. (November 2022) - Isba, Rachel; Brennan, Louise; Davies, Nigel; Knight, Jo
Abstract: Background: In 2019, the UK lost its WHO measles-free status, due to circulating measles virus and suboptimal coverage with the measles, mumps, and rubella (MMR) vaccine. The National Health Service (NHS) schedule recommends MMR vaccines at age 12 and 40 months. In England in 2020–21, MMR coverage did not meet the 95% target for herd immunity. This work is part of a project to develop a vaccination intervention delivered in the paediatric emergency department (PED). The aim of this study was to quantify unmet MMR-related vaccination need among PED attendees. Methods: This cross-sectional, single-centre observational study collected data on children (aged 1–5 years) attending a large district general PED in Greater Manchester, UK, from Oct 1 to Oct 31, 2021, with data collected on a single occasion. Ethics approval was for an opt-out approach. Vaccination data were extracted from individual electronic summary care records, as part of the primary care record visible within secondary care. Coverage in the study population was compared with data for the northwest of England from the Cover of Vaccination Evaluated Rapidly surveillance scheme for the period April 1, 2020 to March 31, 2021. χ 2 tests were used to examine differences in proportions vaccinated. Findings: 1059 children aged 1–5 years attended the PED in October, 2021, and data for 977 children were included in this study. Among all children, 638 (65·3%) had at least one dose of MMR recorded in their summary care record. The most similar regional comparator was first-dose MMR by the age of 5 years, which was administered in 86 678 (95·2%) of 91 023 children in 2020–21 (p<0·0001). In our cohort, among eligible children older than 40 months (n=339), only 66 (19·5%) had received both MMR doses, compared with regional coverage (by age 5 years) in 79 535 (87·4%) of 91 023 children (p<0·0001). A power calculation showed 577 participants were needed to detect a 5% difference in second-dose MMR. Interpretation: Children younger than 5 years attending the PED had low rates of age-appropriate MMR vaccination coverage, suggesting considerable unmet need in these PED attendees. Other work within this project looks at tetanus coverage and sources of vaccination data. Funding: None.